Squamous cell carcinoma arising over seborrhoeic keratosis - A rare presentation - Mrinal Gupta (Our Dermatology Online, 2018)
Seborrhoeic keratoses (SKs)are common skin lesions that occur with increasing age. Usually they have a benign course but varying degrees of squamous atypia have been seen. Bowenoid transformation of benign SKs into squamous cell carcinoma in situ has been documented but the development of basal or squamous cell carcinoma in a seborrhoeic keratosis is rare. Herein, we report a case of squamous cell carcinoma arising over a long-standing seborrhoeic keratosis in 70-year old male, which was managed with a wide surgical resection.